Hadis dan dan Kesalehan Ekoteologi: Studi Living Hadis pada Ceramah Fahrudin Faiz tentang Menjaga Alam - Aldi Wikaldi; Rasyid Alhafizh (JOURNAL SAINS STUDENT RESEARCH, 2025)
The global environmental crisis demands a multidimensional approach that is not only technical but also spiritual and ethical. This article examines the role of digital preaching in embedding Islamic ecotheology values through an analysis of Fahrudin Faiz’s sermons on his digital channel. Employing a netnographic approach, this study explores how Faiz interprets and actualizes the Prophet Muhammad’s hadiths related to environmental care in the context of contemporary ecological crises. The findings show that the sermons successfully integrate the principles of tauhid (divine unity), khilafah (stewardship), amanah (moral responsibility), and mizan (balance) as moral and spiritual foundations for environmental sustainability. However, digital preaching faces challenges in maintaining message consistency and motivating behavioral change among a diverse audience. This research emphasizes the importance of adaptive communication strategies and collaboration among preachers, religious institutions, and communities to strengthen digital ecological preaching movements. These findings contribute to the understanding of Islamic ecotheology as an ethical solution to environmental crises and the role of digital media in socio-ecological transformation.